الصراع على المضائق الدولية (دراسة حالة مضيق هرمز - رحال, محمد (جامعة الوادي University of Eloued, 2017)
تعد الاعتبارات الجيوسياسية والجيوستراتيجية لأي إقليم ذات دور كبير في تحديد ماهية العلاقات البينية لدول هذا الإقليم وأشكالها، وآليات التفاعل التي تحكم هذه العلاقات وتحديد مساراتها واتجاهاتها وأهدافها، فالعالقات الدولية عادة هي انعكاس لمتطلبات واقع جغرافي وسياسي واقتصادي معين يفرض على أطراف هذه العلاقة طبيعة السلوك السياسي المتبع في علاقاتها مع الأطراف الأخرى، سواء على الصعيد الإقليمي أو الدولي. لقد استطاعت منطقة الخليج العربي أن تقفز خلال العقود الثلاثة الأخيرة إلى قمة الاهتمامات الدولية لعوامل عديدة يمكن أن نعزوها بالأساس إلى ثقلها النفطي الكبير، وإلى موقعها الاستراتيجي المتميز، فضلا على إيقاع الأحداث التي استقطب اهتمام العالم كله، هو وجود مضيق هرمز الذي يشرف على مرور حوالي 40% من النفط العالمي. تذهب الدراسة إلى التركيز على أهمية الجيوسياسية والجيوستراتيجية لقيمة هذا الموقع كأحد العناصر الرئيسية في التوازن الاستراتيجي الدولي، وأبعاد توظيفها في نطاق استراتيجيات الكلية الشاملة للقوى الدولية الكبرى، وصراعات القوى الإقليمية للسيطرة عليه. وتحاول الدراسة تحديد مفهوم الجغرافيا السياسية، وعلاقاتها بالجيوبوليتيك وتطورها التاريخي وآلية تحول جغرافيا السياسة المعاصرة إلى جيوبوليتيك السياسة للجغرافيا، والتركيز على واقع الجغرافية السياسية بصThe geopolitical and geostrategic considerations of any region have a major role in determining the interrelationship between the countries and forms of this region, the interaction mechanisms that govern these relations, their paths, directions, and goals. International relations are usually a reflection of the requirements of a particular geographical, political and economic reality. In their relations with other parties, both at the regional and international levels. Over the past three decades, the Arabian Gulf has been able to rise to the top of international concerns for several factors that can be attributed mainly to its great oil weight, its strategic location and the events that have attracted the attention of the entire world. The Strait of Hormuz, 40% of world oil. The study focuses on the importance of geopolitics and geostrategic value of this site as one of the main elements of the international strategic balance, and the dimensions of its employment within the overall macro strategies of the major international powers and the conflicts of regional powers to control it. The study attempts to define the concept of geopolitics, its relations with geopolitics, its historical development, and the mechanism of geopolitics turning geopolitics into geopolitics, focusing on the reality of geopolitics in general, and the Strait of Hormuz in particular and the regional system of the Arabian Gulf. .
أنظمة سياسية مقارنة وحكم راشد
Keywords: المضائق الدولية، الجغرافيا السياسية، الجيوبوليتيكا، مضيق هرمز; International Straits, Geopolitics, Geopolitics, Strait of Hormuz